Low radar cross section HIS-based phased array radiation and scattering analysis - Singh, Hema.; Singh, Avinash (Boca Raton, FL : CRC Press, 2021)
The design and development of low radar cross section (RCS) phased array has been a challenging subject in stealth technology. The frequency selective surface elements act as absorbers in specific frequency band and facilitate gain enhancement and reduction of antenna RCS. This book presents a comprehensive EM design and analysis of such low-profile patch arrays with high impedance surface-based ground plane. It explains how to determine radiation mode RCS of low-profile antenna arrays with arbitrary configurations. Detailed descriptions of design, workflow of determining radiation and scattering behavior of antenna arrays have been supported with schematics, tables, and illustrations. Aimed at engineers and researchers for RCS, antenna engineers and graduate students in electrical engineering and electromagnetics, it Discusses both radiation and scattering features of both planar and conformal HIS-based low profile antennas Describes the theoretical background, design, simulations and analysis of low RCS phased array in detail Presents the physics behind the resultant radiation and scattering characteristics of designed antenna array Helps readers understand design and analysis of low RCS antenna array without any degradation in its radiation performance Includes figures, schematics and illustrations to provide comprehensive descriptions of both radiation and scattering characteristics of phased arrays of different configurations
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Electricity; TECHNOLOGY / Microwaves; TECHNOLOGY / Remote Sensing; Radar cross sections; Phased array antennas; Signal processing